Extracorporeal Membrane Oxygenation for Acute Toxic Inhalations: Case Reports and Literature Review - Yu, Dun; Xiaolin, Zhang; Lei, Pan; Feng, Li; Lin, Zhang; Jie, Shen (Frontiers in Medicine, 2021)
Previous studies have shown that poisoning is a major threat to human health. Inhalation of acute toxic gas has been linked to serious health consequences. Among the antidotes for poisoning currently used, supportive care is the most common intervention in clinical practice. Severe acute respiratory distress syndrome (ARDS) and/or refractory cardiogenic shock or cardiac arrest caused by toxins are associated with high mortality and are difficult to treat. Extracorporeal membrane oxygenation (ECMO) is an aggressive supportive measure used to manage severely poisoned patients. This study presents two cases of acute toxic gases inhalation, severe ARDS and circulatory instability induced by bromine inhalation, and ARDS induced by nitric acid inhalation which were successfully treated with ECMO. The ECMO techniques used in the animal models and in human cases to treat severe poisoning are described as well as the indications, contraindications, complications, and weaning of ECMO.